Generic Strategies and Competitiveness of Tea Brokerage Firms in Kenya - Peter, Situma Sasaka, Peter, Situma Sasaka (Multidisciplinary Journal of Technical University of Mombasa, 2023)
The general objective of the study was to investigate the effect of generic strategies on the competitiveness of tea brokerage firms in Kenya. The generic strategies used in this study were; cost leadership strategy, differentiation strategy, innovation strategy and focus strategy. The specific objectives of the study were: to determine the effect of cost leadership strategy, differentiation strategy, innovation strategy and focus strategy on the competitiveness of tea brokerage firms in Kenya. The study adopted a mixed research design with the specific research design being a descriptive design and cross-sectional research design. The population of the study comprised of the managers of tea brokerage firms in Kenya. The sampling frame consisted of 60 tea brokerage firms whereby 100 managers formed a sample size which ascertained the effect of competitive strategies on the competitiveness of tea brokerage firms in Kenya. The unit of analysis were the managers. The sampling technique used was stratified random sampling. Primary data was collected by use of questionnaires which were administered through drop and pick method. Reliability was tested using Cronbach’s Alpha. Data was analyzed using both descriptive and inferential statistics through the software SPSS version 24. Descriptive statistics included standard deviations and mean scores. Inferential statistics included Pearson’s correlation and multiple regression analysis for testing of hypotheses. If the p-value was below the significance level (0.05) the study rejected the null hypothesis. The study showed that only two variables had positive and significant effect on Firm Competitiveness, with the most influential being Innovation Strategy which had regression coefficient of 0.572 and a p-value of 0.000 and was also less than 0.005. This was then followed by Cost Leadership Strategy which had regression coefficient of 0.135 and a p-value of 0.005. However, there was no significant relationship between Differentiation Strategy and Firm Competitiveness (0.343), Focus Strategy and Firm Competitiveness (0.417) respectively. This leads to conclusion that Cost Leadership Strategy and Innovation Strategy significantly affects competitiveness of Tea Brokerage firms in Kenya. The study recommends that: Kenyan firms should understand and adopt 2 competitive strategies that have been proven to help them gain a competitive advantage and improve its performance. Therefore, Kenyan firms can wade of competition from their international competitors using proven competitive strategies; and the Kenyan market should foster economic development by encouraging and promoting strategies that ensure the sustainability of tea brokerage firms and SMEs.